Synthesis of 3, 3‐Disubstituted Oxindoles by Palladium‐Catalyzed Asymmetric Intramolecular α‐Arylation of Amides: Reaction Development and Mechanistic Studies. Issue 36 (25th July 2013) - Katayev, Dmitry; Jia, Yi‐Xia; Sharma, Akhilesh K.; Banerjee, Dipshikha; Besnard, Céline; Sunoj, Raghavan B.; Kündig, E. Peter
Abstract Palladium complexes incorporating chiral N‐heterocyclic carbene (NHC) ligands catalyze the asymmetric intramolecular α‐arylation of amides producing 3, 3‐disubstituted oxindoles. Comprehensive DFT studies have been performed to gain insight into the mechanism of this transformation. Oxidative addition is shown to be rate‐determining and reductive elimination to be enantioselectivity‐determining. The synthesis of seven new NHC ligands is detailed and their performance is compared. One of them, L8, containing a tBu and a 1‐naphthyl group at the stereogenic centre, proved superior and was very efficient in the asymmetric synthesis of fifteen new spiro‐oxindoles and three azaspiro‐oxindoles often in high yields (up to 99 %) and enantioselectivities (up to 97 % ee; ee=enantiomeric excess). Three palladacycle intermediates resulting from the oxidative addition of [Pd(NHC)] into the aryl halide bond were isolated and structurally characterized (X‐ray). Using these intermediates as catalysts showed alkene additives to play an important role in increasing turnover number and frequency.